A intertextualidade na produção escrita de estudantes do ensino médio – a linguística do texto e a pesquisa-ação na escola - Santos, Patricia dos (2017)
This master's research has as general goal to investigate whether high school students use the intertextuality in textual productions of the argumentative field, articulating it to their point of view. The specific goals created for this work are: to verify if teaching and production of texts, according to the principles of Text Linguistics, favor the teaching and learning processes in the classroom; to investigate whether the bases of the Process Writing contribute to the development of skills in the written production of the Basic Education students; and to determine action research as a possible methodological support in Portuguese Language classes, in order to enable advances in the textual competence in high school students from a Public School of Santa Maria/RS. This study has theoretical support in: Bakhtin ([1929], 2009 and [1979], 1997), Vygotsky ([1930], 2007, [1934], 1989 and [1988], 2014), Beaugrande & Dressler (1981), Marcuschi (1983, 2012), Fávero & Koch (2012), Koch & Elias (2012), Koch, Bentes & Cavalcante (2012), Thiollent (2011), White & Arndt (1991), Dolz & Schneuwly (2004), among others. This study aims to prioritize the moment of textual production in the classroom, in the opposite shift to regular classes, in order to corroborate the work that has already been elaborated by the school, from reading, debates and argumentation, writing and rewriting. About the results, we are able to say that intertextuality, as a resource of authority, helped the students to defend their points of view in argumentative texts. Related to the production of texts, the students had the opportunity to experience the text as a learning process and the rewriting guided by a joint and dialogical evaluation. In this sense, textual production is conceived as a starting point in Portuguese Language classes, especially with high school students, focusing on the text as a process.